Conflict Management in Health Care Institutions - Vitaliia Koibichuk; Henryk Dzwigol; Svitlana Stenko (Health Economics and Management Review)
Conflicts negatively affect the teamwork atmosphere. They lead to a deterioration of the psychological microclimate and reduce employability and deteriorate workers' health. The authors noted that conflicts arise from different points of view, interests, manners, and management styles of conflict parties. Thus, an essential skill of any health care leader is the ability to prevent conflicts, reduce their negative consequences, resolve disputes, and create an atmosphere of mutual intelligibility. This study is devoted to conducting theoretical and practical research on conflict management in healthcare to form proposals for reducing the conflict level in healthcare institutions. The research uses methods of a systematic approach, sociological survey, testing, questionnaires, systematization, comparison, and logical generalization. The practical analysis of the conflict management process was carried out in the municipal non-profit enterprise of the Sumy Regional Council «Regional Diagnostic Center in Shostka». The study sample consists of ten doctors and ten nurses. This study conducted the following questionnaires: «Are you a conflicted person?»; «Assessment of patients' conflict personality»; «Assessment of personality conflict»; «Assessment of balance in conflicts and propensity to nervous breakdowns», K. Thomas' test «Identification of behaviors in conflict situations», A. Asinger's methods of diagnosing aggression in the relationship. The findings showed that nurses are characterized by a higher level of personal conflict than doctors. Besides, in most conflict situations, health professionals prefer cooperation as a tactic of negotiation in conflicts. However, a third of conflict situations are characterized by the parties' «opposition». The results showed that the most common conflict situations are the doctor-doctor and nurse-nurse. Conflicts between doctor-patient and nurse-patient occurred approximately equally. 75% of respondents indicated an average level of aggression. Based on the obtained results, to prevent and reduce the number of conflicts in health care institutions, the authors emphasized the importance of counseling and psychological work to resolve disputes, creating conditions for positive psychological relations between health professionals and patients, active use of information, communication, social-psychological, organizational technologies of conflict management.